Basic measurements of radiation at station Lauder (1999-08 - 2018-12) - Australian Bureau of Meteorology (PANGAEA, 2025)
This is a compilation of all short-wave and long-wave radiation datasets from Lauder that were published by the Australian Bureau of Meteorology in the frame of BSRN. The data are subject to the data release guidelines of BSRN (https://bsrn.awi.de/data/conditions-of-data-release/).